Relation of Age and Serum Prostatic-Specific Antigen level with Histopathological diagnosis in Transurethral Resection of Prostate specimen, an Experience from Eastern Tertiary Hospital - Shah, Ram Sagar; Pandey, Dipesh Raj (Journal of Nepalgunj Medical College, 2019)
Background: Prostatic Specific Antigen (PSA) is a protease secreted by epithelial cells of prostate. Serum PSA level is increased when the normal structure of gland is destroyed by benign or malignant tumor or inflammation. Though there is established relation between PSA plasma level and age among the two most common prostate diseases (Benign prostatic hyperplasia and Carcinoma Prostate) in the literature, relation has not been explored in our part of the world, therefore, this study was done to see the relation between age and PSA amount with Prostate diseases. Material and Methods: This was a Cross-sectional study conducted in a tertiary hospital, Nobel Medical College Teaching Hospital from January 2017 to December 2018. Ethical clearance was obtained from Institutional Review Committee (IRC). All the cases of prostate diseases presenting to urology department undergoing transurethral resection of the prostate (TURP) were included. Histopathology report of TURP specimen were collected from department of pathology and the relationship between diagnosis, PSA level and age were established. Results: BPH was the most common diagnosis (72.41%). Age of BPH patients ranged from 48-78 years and mean age with SD was 60.56±7.32. Median age with interquartile range was 61.00. Similarly, in the BPH group, PSA value ranged between 0.80-15.40 ng/ml with mean PSA value along with SD being 5.64±4.16 ng/ml. Similarly, Median PSA value with interquartile range was 4.20ng/ml. Carcinoma Prostate (27.59%) was the second most common diagnosis. Histological type of all cases diagnosed as cancer was adenocarcinoma. Their age ranged between 54-83. Their mean age with SD was 67.67±7.68. Similarly, Median age with interquartile range was 68.00. PSA value in this group ranged between 8.50-147.30 ng/ml. Again, the mean PSA value with SD is 55.72±33.40 ng/ml. Similarly, Median PSA value with interquartile range is 54.30 ng/ml. Conclusion: PSA level in the blood of men over 40years is highly correlated with a Age, irrespective of diagnosis. In above 40 age group, with advancing age, Carcinoma Prostate becomes more and more common diagnosis than BPH. Similarly, average PSA level is higher in Carcinoma Prostate than BPH.